Pengaruh Corporate Social Responsibility dan Tax Avoidance terhadap Nilai Perusahaan melalui Earnings Management sebagai Variabel Intervening - Novyarni, Nelli; Cahyasari, Ika; Harni, Reni; Kartijo, Kartijo; Rahayu, Dwi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This research aims to analyze the influence of Corporate Social Responsibility (CSR) and Tax Avoidance on company value with earnings management as an intervening variable. The objects of this research are companies listed on the Indonesian Stock Exchange in the property and real estate sector during the 2018-2021 period. This research uses quantitative methods with a sample of 59 companies, of which 12 were selected and analyzed using Eviews 12. The research results show that Corporate Social Responsibility (CSR has a significant influence on earnings management. On the other hand, Tax Avoidance has no effect on earnings management. Apart from that , company value is not influenced by Corporate Social Responsibility (CSR), Tax Avoidance, or earnings management. This research also finds that earnings management cannot intervene in the relationship between Corporate Social Responsibility (CSR) and company value, nor the relationship between Tax Avoidance and. company value. These findings provide insight into the relationship between Corporate Social Responsibility (CSR), Tax Avoidance, and earnings management in the context of property and real estate companies in Indonesia during the 2018-2021 period. Implications of the findings The insignificant influence of CSR disclosure on company value is also caused by low CSR disclosure, investor behavior, and CSR variables that cannot be measured directly and the insignificant influence of tax avoidance on company value implies that tax avoidance efforts cannot increase company value.